Field evaluation of the P22 ELISA for diagnosis of caprine tuberculosis in an endemic area - Velasco, Carlos; Ortega, Javier; Alvarez, Julio; Infantes Lorenzo, Jose Antonio; Moreno, José C.; Sanz, Cristina; Romero, Beatriz; de Juan, Lucia; Dominguez, Lucas; Dominguez, Mercedes; Moreno, Inmaculada; Roy, Alvaro; et al. (Frontiers in Veterinary Science, 2025)
Animal tuberculosis (TB) affects a wide range of domestic species, including goats. TB eradication programs in goats are based on cell-based techniques such as the single and comparative intradermal tuberculin test (SITT and CITT, respectively). In recent years, an ELISA technique based on the P22 protein complex (P22 ELISA), has emerged as a valuable tool for TB diagnosis. The aim of the study was to evaluate the performance of the P22 ELISA in the context of a caprine TB eradication program using serum, individual milk and bulk tank milk (BTM) samples in order to define its usefulness in classifying herds compared to SITT and CITT. Samples from 53 herds categorized based on the detection of CITT reactors (16 high-risk herds, with one or more CITT reactors, and 37 low-risk herds, with only CITT-negative goats) were analyzed. Reactors in the P22 ELISA were detected in a higher number of high-risk herds using both serum (87.5%) and individual milk (81.3%) compared to SITT (75.0%) and CITT (31.3%), while the use of BTM led to the detection of 33.3% of the herds. Individual apparent prevalence was higher using the P22 ELISA in both serum (11.0%) and milk (15.0%) compared to the SITT (6.8%) and CITT (2.5%), with also a significantly (p < 0.001) higher number of reactors in individual milk compared with the serum. Similarly, all six herds with MTBC confirmed infection showed reactors to the SITT, CITT, and individual serum and milk P22 ELISA (2 out of 5 detected using BTM), although the highest reactivity was observed using individual milk samples. In the low-risk herds, a lower number of positive herds and animals were found with the P22 ELISA using serum or individual milk (51.4%) compared to SITT (59.5%) while using CITT only 2.7% of the herds were positive and none reacted to the P22 ELISA in BTM samples. This study shows that the P22 ELISA, using serum and especially individual milk samples, could be a complementary tool for maximizing the sensitivity of intradermal testing within the framework of a caprine TB eradication program.